Flood preparedness and utilization of early warning systems among households in selected flood-prone areas in Tagum City, Davao Del Norte - Boyeth C. Pelone; Anabeth Jean P. Arellano (Davao Research Journal)
Flooding, a widespread natural disaster, poses significant threats globally, impacting infrastructure, property, and lives. Barangay San Miguel, Tagum City, Davao Del Norte, emerges as a particularly vulnerable area with substantial repercussions for its surrounding communities. Hence, assessing household preparedness and the effectiveness of early warning systems is crucial. A survey of randomly selected respondents, using the Slovin formula, evaluated indicators like first aid kits, evacuation plans, food supplies, and participation in seminars and training. The findings indicate commendable overall household preparedness yet reveal deficiencies in capability building and the lowest mean value in flyers and leaflets for the early warning system. Policymakers should prioritize targeted training programs to enhance knowledge and skills while allocating resources to strengthen early warning systems, focusing on effective information distribution through flyers and leaflets. This holistic approach enhances community resilience and reduces vulnerability to flooding in Barangay San Miguel and similar areas.